2010
DOI: 10.1175/2009jtecha1274.1
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Wind Velocities in Mountain Lee Waves Using Sailplane Flight Data*

Abstract: Mountain lee waves are a form of atmospheric gravity wave that is generated by flow over mountain topography. Mountain lee waves are of considerable interest, because they can produce drag that affects the general circulation, windstorms, and clear-air turbulence that can be an aviation hazard, and they can affect ozone abundance through mixing and inducing polar stratospheric clouds. There are difficulties, however, in measuring the three-dimensional wind velocities in high-altitude mountain waves. Mountain w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Although measurements of either ground velocity and airspeed, or ground velocity and heading, give a one-parameter family of solutions for the wind speed, we have shown that using the fact that the wind field in high-altitude mountain wave varies slowly over the flight path allows estimates of the wind velocity to be determined from these kinds of data. 7,8 However, in the vast majority of cases, the instrumentation installed in most sailplanes records only the GPS position during a flight so that only the ground velocity is known. Determination of the wind velocity is then highly underdetermined and there is a two-parameter family of solutions.…”
Section: Problem Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although measurements of either ground velocity and airspeed, or ground velocity and heading, give a one-parameter family of solutions for the wind speed, we have shown that using the fact that the wind field in high-altitude mountain wave varies slowly over the flight path allows estimates of the wind velocity to be determined from these kinds of data. 7,8 However, in the vast majority of cases, the instrumentation installed in most sailplanes records only the GPS position during a flight so that only the ground velocity is known. Determination of the wind velocity is then highly underdetermined and there is a two-parameter family of solutions.…”
Section: Problem Characteristicsmentioning
confidence: 99%
“…4(a) shows a histogram of airspeed data measured during the wave flight described in Ref. 7. We fitted a variety of probability distributions to the histogram shown in Fig.…”
Section: Flight Data and Modelmentioning
confidence: 99%